Climatic changes and the energy infrastructure in the Russian Arсtic - Solovyev , Dmitry; Shilova , Liubov; Разоренова , Ольга (project baikal, 2022)
The current state and topical issues of building the energy infrastructure of the Russian Arctic and its protection under the influence of an extreme climate are considered. Infrastructure projects implemented in the Arctic regions of Russia within the framework of the “energy transition” concept are analyzed. The importance of considering climatic and environmental factors, the recreational nature of the place and the need to search for new solutions in countering modern climatic challenges are emphasized. The authors also discuss the possibilities of implementing new approaches in the design of capital construction projects based on intelligent-digital systems of construction and energy modeling, as well as their role in increasing the sustainability of the energy infrastructure of the region.
Keywords: Russian Arctic; sustainable development; environment; climate; ecology; tourism; information modeling; energy modeling